2018
DOI: 10.1182/blood-2018-06-854711
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function zinc finger mutation in the EGLN1 gene associated with erythrocytosis

Abstract: Mutations in the EGLN1 (also known as PHD2) gene are associated with erythrocytosis. 1 The encoded protein, PHD2, is a central cellular oxygen sensor that hydroxylates the a subunit of the hypoxia inducible factor (HIF) transcription factor complex, marking it for degradation. 2-4 HIF controls red cell mass principally through upregulation of the ERYTHROPOIETIN (EPO) gene. 5 All functionally characterized erythrocytosis-associated mutations in the EGLN1 gene described to date are heterozygous loss-of-function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…S6E). PHD2 contains a highly conserved myeloid nervy deformed epidermal autoregulatory factor 1 homolog (MYND)–type zinc finger ( 28 , 29 ) with two conserved CXXC (two cysteines separated by two other residues) domains C21/24 and C33/36; the two mutations that affect PHD2 activity fall within one or the other of these conserved domains. To determine whether the identified cysteine residues within PHD2 were important for association with HIF-1a, we assessed the interaction of mutant or WT PHD2 with full-length glutathione S -transferase (GST)–HIF-1α.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6E). PHD2 contains a highly conserved myeloid nervy deformed epidermal autoregulatory factor 1 homolog (MYND)–type zinc finger ( 28 , 29 ) with two conserved CXXC (two cysteines separated by two other residues) domains C21/24 and C33/36; the two mutations that affect PHD2 activity fall within one or the other of these conserved domains. To determine whether the identified cysteine residues within PHD2 were important for association with HIF-1a, we assessed the interaction of mutant or WT PHD2 with full-length glutathione S -transferase (GST)–HIF-1α.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its C-terminal PHD domain, PHD2 also has an N-terminal, evolutionary-conserved, MYND-type zinc finger, a feature that is absent in both PHD1 and PHD3 ( 28 , 29 ). The zinc finger of PHD2 is essential for efficient hydroxylation of HIF-1α ( 11 , 28 , 29 ). Supporting the essentiality of the zinc finger, we found that H 2 S persulfidates PHD2 at five different cysteine residues, two of which are within the zinc finger motif.…”
Section: Discussionmentioning
confidence: 99%
“… 76 Studies are also ongoing for another CD33/CD3 bispecific cell engager, AMV564, which demonstrated safety and antileukemia activity in a first-in-human trial in patients with RR AML. 77 …”
Section: Emerging Immunotherapies For the Treatment Of Patients With mentioning
confidence: 99%
“…Conversely, PHD1 and PHD3 deletions are not lethal, and have only limited tissue specific impact, as exhibited by their effect on cellular metabolism in skeletal muscle and altered blood pressure in the central nervous system, respectively [26,27]. Moreover, PHD2 differs from PHD1 and PHD3 in its N-terminal zinc finger, which favors recruitment of the HSP90 machinery, facilitating HIFα hydroxylation [28,29]. In turn, PHD1 and PHD3 can also be regulated by hypoxia inducible E3 ubiquitin ligases: the SIAH proteins [30].…”
Section: Hif Transcription Factors and Their Modulatorsmentioning
confidence: 99%